Comparative cytogenetic mapping of Sox2 and Sox14 in cichlid fishes and inferences on the genomic organization of both genes in vertebrates - Mazzuchelli, Juliana [UNESP]; Yang, Fengtang; Kocher, Thomas D.; Martins, Cesar [UNESP] (Springer, 2011)
To better understand the genomic organization and evolution of Sox genes in vertebrates, we cytogenetically mapped Sox2 and Sox14 genes in cichlid fishes and performed comparative analyses of their orthologs in several vertebrate species. The genomic regions neighboring Sox2 and Sox14 have been conserved during vertebrate diversification. Although cichlids seem to have undergone high rates of genomic rearrangements, Sox2 and Sox14 are linked in the same chromosome in the Etroplinae Etroplus maculatus that represents the sister group of all remaining cichlids. However, these genes are located on different chromosomes in several species of the sister group Pseudocrenilabrinae. Similarly, the ancestral synteny of Sox2 and Sox14 has been maintained in several vertebrates, but this synteny has been broken independently in all major groups as a consequence of karyotype rearrangements that took place during the vertebrate evolution.
Keywords: Cichlidae; genome evolution; molecular cytogenetics; chromosome